Albania in the Focus of World Press in Years 1970-1973 Man Directions on Assessment and Diplomatic Relations - Sallata, Ilir; Lazimi, Mirela (Richtmann Publishing, 2012)
Albania's communist system coincides with the years 1944-1990.Albanian Communist Party victory of 1944 until the year1948 was oriented entirely toward Yugoslavia. It got away from the chauvinist policies of its malicious, closely related to the SovietUnion. To keep the